1997
DOI: 10.1109/82.644563
|View full text |Cite
|
Sign up to set email alerts
|

Statistically optimum pre- and postfiltering in quantization

Abstract: Abstract-We consider the optimization of pre-and postfilters surrounding a quantization system. The goal is to optimize the filters such that the mean square error is minimized under the key constraint that the quantization noise variance is directly proportional to the variance of the quantization system input. Unlike some previous work, the postfilter is not restricted to be the inverse of the prefilter. With no order constraint on the filters, we present closed-form solutions for the optimum pre-and postfil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…From this point on, the problem under study is very similar to the one analyzed recently in [20], and, in fact becomes exactly the same by setting and to unity in (28). We will therefore omit the proofs of the upcoming theorems and refer to [20]. …”
Section: To (27) the Resulting Expression Is (26)supporting
confidence: 50%
See 1 more Smart Citation
“…From this point on, the problem under study is very similar to the one analyzed recently in [20], and, in fact becomes exactly the same by setting and to unity in (28). We will therefore omit the proofs of the upcoming theorems and refer to [20]. …”
Section: To (27) the Resulting Expression Is (26)supporting
confidence: 50%
“…6 can be obtained again as a special case by setting in (14). The optimum prefilter will then have the following magnitude squared response: (20) and can be regarded as a multirate extension of the half whitening filter [15]. Using (20), we can derive an interesting expression for the coding gain of the scheme of Fig.…”
Section: A Case Where the Postfilter Is The Inverse Of The Prefiltermentioning
confidence: 99%
“…In [11], it is shown that halfwhitening prefilters and reciprocal postfilters maximize the coding gain of arbitrary orthonormal filter-banks using arbitrary quantizers. The optimization of arbitrary quantizers is also addressed in [12]. Pre-and post-filters optimizing the quantizer performance are determined under the assumption that the quantizer noise is uncorrelated with the quantizer input.…”
mentioning
confidence: 99%
“…For simplicity, the analysis and synthesis filters are often chosen to satisfy an orthonormality or biorthogonality condition. If no other restrictions are put on the filters, then the optimal choice for these filters is known (see [5,8,1] for the orthonormal case and [6,9,4] for the biorthogonal case). In the orthonormal case, the optimal solution is an infinite order principal component filter bank (PCFB) [8,1], whereas in the biorthogonal case, the optimal filter bank is a PCFB with a parallel bank of half-whitening filters in the middle of the system [9,4].…”
Section: Introductionmentioning
confidence: 99%